Find x such that log3(2x-1)=1+log2(x+1)?

  1. 👍
  2. 👎
  3. 👁
  1. log3(2x-1)=1+log2(x+1)
    2x-1 = 3*3^log2(x+1)
    This does not yield to algebraic solution

    However, if you had a typo for
    2x-1 = 3(x+1)
    x = -4
    But again, that has no real solution, since the logs are undefined.

    1. 👍
    2. 👎

Respond to this Question

First Name

Your Response

Similar Questions

  1. maths

    express log9 in terms of log3 x and log3 y and solve for x and y simultaneously

  2. calculus

    1) Solve for x in terms of k: log3(x) + log3(x+7) = k; 3 is the base 2) e^(x+5) = e^(x) + 6, solve for x. Please help, I have no idea how to do these and I've tried several times!

  3. Algebra II

    Please check answers: Use the equation of the exponential function whose graph passes through the points (0,-2) and (2,-50) to find the value of y when x= -2. My answer: -2/25 Solve 64^x/=5/2 Thanks.

  4. trig

    solve for x log4 64+ log2 2 ________________ =x log3 81

  1. math

    express log2+log3 as a single logarithm

  2. math/algebra

    solve the equation log2(3x-2) - log2 (x-5)=4

  3. Math

    Given that log3=0.4771 and iog5=0.6990 evaluate the value of log1.35+log2.25

  4. Algebra 1

    Explain the differences between solving these two equations: •log3(x - 1) = 4 AND log3(x - 1) = log34 I think it has to deal with the formulas?

  1. PreCalculus

    Write each expression as a sum or difference of logarithms. Express powers as factors. log2(x^3/x - 3) x > 3 Answer: 3 log2x - log2 (x-3) Could someone show me the steps to get to this answer?

  2. Math

    Given that x=log3^5 and y=log3^2, rewrite log3^60 in terms of x and y.

  3. Math

    log2√36 - log2√72 I am not sure how to do this question. I need an explanation.

  4. math

    solve the equation log2(x+4)-log4x=2 the 2 and 4 are lower than the g This is what I got: log2(x+4)+log2(4^x)=2 log2((x+4)*4^x)=2 4^x(x+4)=4 x=0 is a solution???

You can view more similar questions or ask a new question.